2008
DOI: 10.1161/strokeaha.106.476648
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Administration of Abciximab for Treatment of Patients With Acute Ischemic Stroke: Results of an International Phase III Trial

Abstract: Background and Purpose-A previous randomized, placebo-controlled, double-blind study suggested that abciximab may be safe and effective in treatment of acute ischemic stroke. The current phase 3 study was planned to test the relative efficacy and safety of abciximab in patients with acute ischemic stroke with planned treatment within 5 hours since symptoms onset. Methods-An international, randomized, placebo-controlled, double-blind phase 3 trial tested intravenous administration of abciximab in 2 study cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
197
1
15

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(220 citation statements)
references
References 25 publications
7
197
1
15
Order By: Relevance
“…31 Because platelet activation is a key step in thromboembolism in the reocclusion of an in situ steno-occlusive lesion, [31][32][33][34] intravenous or intra-arterial glycoprotein IIb/IIIa inhibitors could be effective for preventing reocclusion. 32,34 On the basis of the findings of the Abciximab in Emergency Treatment of Stroke Trial, which showed an increased rate of symptomatic or fatal intracranial hemorrhage, 35 we used intravenous or intra-arterial tirofiban in our study only when no contraindication existed.…”
Section: Discussionmentioning
confidence: 99%
“…31 Because platelet activation is a key step in thromboembolism in the reocclusion of an in situ steno-occlusive lesion, [31][32][33][34] intravenous or intra-arterial glycoprotein IIb/IIIa inhibitors could be effective for preventing reocclusion. 32,34 On the basis of the findings of the Abciximab in Emergency Treatment of Stroke Trial, which showed an increased rate of symptomatic or fatal intracranial hemorrhage, 35 we used intravenous or intra-arterial tirofiban in our study only when no contraindication existed.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the AbESTT II trial, a phase III multicenter randomized double-blind placebo-controlled study evaluating the safety and efficacy of abciximab in acute ischemic stroke treated within 6 hours after stroke onset or within 3 hours of awakening with stroke symptoms, was stopped early due to high rates of sICH or fatal ICH in the abciximabtreated patients (5.5% versus 0.5%, P ϭ .002). 35 The data for the use of GP IIb/IIIa inhibitors in conjunction with IAT are even more scant and are limited to case reports. [36][37][38][39][40][41] Deshmukh et al 38 reported 21 patients with large-vessel occlusion refractory to IAT with rtPA who were treated with IV and/or IA abciximab, eptifibatide, or tirofiban.…”
Section: Adjunctive Therapymentioning
confidence: 99%
“…In stroke patients early data for the use of abciximab had indicated a safe use (Burton 2003). A phase-III-study, however, had to be stopped due to an increased bleeding rate and no sufficient efficacy (Adams et al 2008). For the competitive receptor antagonist tirofiban until now only smaller studies without safety concerns are available, also in combination with rtPA (Junghans et al 2001, Seitz et al 2003) -further studies are pending (SATIS).…”
Section: Gp-iib / Iiia-antagonistsmentioning
confidence: 99%